First Nation retained sovereignty: an inherent right to participate in and regulate gaming economies - Harris, Bartley (2015)
First Nations in Canada and tribes in the United States share similar histories from pre-contact to present day. Indigenous peoples met newcomers from overseas and established relationships of trade and military alliance. This relationship changed over time, owing to many factors, not limited to shifts in demographics as a result of waves of immigration, war and disease. The emerging settler societies of Canada and the United States have maintained similar, but differing, relationships with the Indigenous nations on the respective sides of the present day border. The differences emerge as result of the manner in which the settler colonies severed their relationship with the British Empire. In the United States, independence occurred in 1776 during a time when tribal nations were relied upon for military strength and when tribal political autonomy was self-evident. Not surprisingly, the newly formed union did not purport to exercise dominion over the tribes. Rather, the United States recognized tribal sovereignty. Since then, relying on notions of racial superiority, both the United States and Canada have wrested fundamental tenets of democracy to conclude that unilateral dominion is not only legal, but morally correct. This thesis seeks to support the position that tribal and First Nation sovereignty has not been extinguished and First Nations continue to possess inherent rights of self-government and sovereignty. October 2015